Menumbuhkan Perilaku Positif Pada Karyawan: Studi Korelasi Lingkungan Kerja dan Organizational Citizenship Behavior - Christanti, Ariendra; Satwika, Pratista Arya; Astriana, Selly (Psikologi UHAMKA, 2023)
Employees are one of the resources that can help the company achieve its goals. This can be occurred by employees carrying out roles outside their main duties (extra roles) known as organizational citizenship behavior. The emergence of organizational citizenship behavior in employees can be influenced by the company's work environment. This study aims to determine whether there is a positive relationship between the work environment and organizational citizenship behavior in employees. The research was conducted at a tourism company in Central Java. Respondents involved in this study were 59 employees consisting of 47 male respondents and 12 female respondents. The sampling technique used is a population study or census study, so that all employees are the research sample. The research instruments were the Organizational Citizenship Behavior Scale (α = 0.801) and the Work Environment Scale (α = 0.836). Product moment correlation by Karl Pearson was used to test the research hypothesis. The results of analysis stated that there was a significant and positive relationship between the work environment and organizational citizenship behavior (r = 0.800; p <0.05). Based on these results it can be concluded that the better work environment built by the company for employees will increase organizational citizenship behavior shown by employees. In addition, it was also found that the non-physical work environment has a greater influence on organizational citizenship behavior of employees (β = 0.538; p<0.05) than the physical work environment (β = 0.515; p<0.05).